Tailoring of the polarization-resolved second harmonic generation in two-dimensional semiconductors - Psilodimitrakopoulos Sotiris; Ilin Stepan; Zelenkov Lev E.; Makarov Sergey; Stratakis Emmanuel (Nanophotonics, 2024)
Second harmonic generation is a non-linear optical phenomenon in which coherent radiation with frequency ω interacts with a non-centrosymmetric material and produces coherent radiation at frequency 2ω. Owing to the exciting physical phenomena that take place during the non-linear optical excitation at the nanoscale, there is currently extensive research in the non-linear optical responses of nanomaterials, particularly in low-dimensional materials. Here, we review recent advancements in the polarization-resolved second harmonic generation propertied from atomically thin two-dimensional (2D) crystals and present a unified theoretical framework to account for their nonlinear optical response. Two major classes of 2D materials are particularly investigated, namely metal chalcogenides and perovskites. The first attempts to tune and control the second harmonic generation properties of such materials via the application of specific nanophotonic schemes are additionally demonstrated and discussed. Besides presenting recent advances in the field, this work also delineates existing limitations and highlights emerging possibilities and future prospects in this field.